PROFILE OF OCULAR TRAUMA IN UTTARAKHAND, A HOSPITAL BASED STUDY - Dhasmana, Renu; Bahadur, Harsh; Jain, Kunal (Indian Journal of Community Health, 2012)
Background: Although ocular trauma is preventable public health problem throughout the world it is still one of the common causes of ophthalmic morbidity and monocular blindness. There are no published studies on pattern and severity of ocular trauma in Uttarakhand. The present study analyzes the pattern and visual outcome of ocular trauma in this region. Methods: Study design: Prospective hospital-based study. Settings: Patients of ocular trauma presenting to Ophthalmology OPD and emergency department of Himalayan Institute of Medical Sciences, Dehradun. Participants: All ocular injury patients seen for the first time during the period January to December 2008. Results: A total of 88 patients, and 103 eyes, were studied. Men had two fold higher rate of ocular injury than women. The mean age of presentation was 31.2 + 13.6 years (range: 6 - 80 years). The predominant age group of patients was 21-40 years, 55.29 % (n = 47). Eye injuries related to road traffic accident were seen in 37.86% of eyes. Industrial workers were more frequently involved in ocular trauma (23.86%). Closed globe injuries were noted in 55 eyes (53.39%) and open globe injuries were noted in 40 eyes (38.83%). Eight eyes (7.76%) suffered from chemical injuries. The initial presenting visual acuity of patients with blunt ocular trauma was better than penetrating injury. Eye with better visual acuity at presentation had better visual prognosis at 6 months. Conclusion: Ocular injuries were common in young males. Road traffic accidents related eye injuries were noted in significant number of cases. Strict implementation of traffic rules, health education and preventive strategies may help to decrease the occurrence of ocular injuries.